The Architectures of the Designed Human: A Legal and Scientific Analysis of Germline Genome Editing (Maharaja Surajmal Institute Law Journal, 2026)
The convergence of reproductive biology and genomic engineering has  birthed a legal and ethical singularity: the potential to design the genetic  constitution of future human generations. This research paper, situated  at the intersection of Law and Emerging Technology, provides an exhaus tive examination of the phenomenon colloquially termed the “designer  baby”—specifically, the application of Heritable Human Genome Editing  (HHGE). We traverse the molecular intricacies of CRISPR-Cas9 mediated  double-strand breaks and homology-directed repair, establishing the scientific baseline necessary for legal adjudication. The analysis proceeds to  dissect the regulatory vacuum exposed by the He Jiankui affair, contrast ing the “illegal medical practice” verdict with the subsequent amendment  to the Criminal Law of the People’s Republic of China (Article 336-1). A  comparative legal framework scrutinizes the permissive licensure model  of the United Kingdom’s Human Fertilisation and Embryology Authority  (HFEA), the funding-based prohibition in the United States, and the dig nity-based bans of the European Oviedo Convention. Centrally, this report  evaluates the Indian legal landscape, interrogating the applicability of the  Environment (Protection) Act, 1986, to human biological materials and  analyzing the constitutional tension between reproductive privacy under  Article 21 and the state’s parens patriae interest in preserving the unadul terated human gene pool. We conclude that current statutory frameworks  are ill-equipped to manage the transition from negative selection (PGD)  to positive modification, necessitating a sui generis biomedical jurispru dence.
Keywords: reproductive; biology; genomic; engineering; ethical; singu larity